EFFECT OF CRUSHED DOUM PALM SHELL AS PARTIAL REPLACEMENT OF COARSE AGGREGATE IN CONCRETE - Liman, A. Z.; Adagba, T.; Umar, H. A. (FUDMA Journal of Sciences, 2021)
The use of alternative materials in place of natural aggregate in concrete production has been getting attention all around the globe; this makes concrete a sustainable and environmentally friendly construction material. In this study the use of crushed doum palm shell (CDPS) as partial replacement for coarse aggregate in concrete production was investigated. The concrete grade 30 was used for the research with a water /cement ratio of 0.45. The control sample contained normal concrete ingredient cement, fine aggregate and coarse aggregate. The CDPS replacement by weight was varied at 5%, 10%, 15%, 20%, and 25% respectively for the test sample. The 28-day compressive strength of the concrete using Doum palm shell aggregate was found to be 28.0 and 20.2 MPa at 5 and 10% replacement under full water curing and it satisfies the requirement for structural lightweight concrete which was more than 17MPa. The study recommended replacement of coarse aggregate up to a maximum of 10 % crushed doum palm shell for structural light weight concrete and it encourage the use of agricultural wastes in construction as an environmental protection and cost reduction measure. However, results from laboratory investigations indicated that crushed doum palm shell (CDPS) has good potential as a coarse aggregate for production of structural lightweight concrete, especially for low-cost housing and also for use in earthquake prone areas.
Keywords: Doum, Palm shell, concrete, workability, compressive strength